Soil Phosphorus Fractionation as Affected by Paper Mill Biosolids Applied to Soils of Contrasting Properties - Zhang, Xiangru; Gagnon, Bernard; Ziadi, Noura; Cambouris, Athyna N.; Alotaibi, Khaled D.; Hu, Zhengyi (Frontiers in Environmental Science, 2020)
Industrial by-products such as paper mill biosolids (PBs) have been used as fertilizers and amendments in agriculture for many decades. However, their content of plant essential nutrients including phosphorus (P) varies largely with sources, and availability of these nutrients once applied to soil still remains unknown. Five PBs differing in their C/N ratio (12–47) were used in an incubation study to assess the P forms and availability from both PBs and PB-amended soils. Biosolids were added to three contrasting soils varying in texture and pH in 500-ml jars at the rate of 50 Mg wet ha–1, supplying between 45 and 112 kg total P ha–1. An unfertilized control and a mineral NP treatment (30 kg P ha–1) were also included. Biosolids and soil P fractions were determined by a modified Hedley fractionation method following 2 and 16 weeks of incubation. Phosphorus forms in PBs varied across type of materials with labile P ranging from 20 to 72% and organic P (Po) ranging from 28 to 66% of total P. Soil incubated with PB showed changes in all P fractions due to amendment, soil type, and duration of incubation. Resin-P and labile P, the most available forms, were significantly higher with addition of high PB–P content. Soil labile P represented up to 50% of total P added by PB. Overall, most inorganic P (Pi) fractions and labile P further increased with incubation duration. Close relationships were established between resin-P and labile P content in PB and the increases of those fractions in incubated soils, notably after 2 weeks. The P recovery as labile P represented on average 34% of total P added or 68% in terms of mineral P. We concluded that PB could be used as an efficient source of P for fertilizing crops.